Vermicompost on the production and nutraceutical quality of jalapeño pepper fruits (Capsicum annuum L.) - Bernardo Espinosa-Palomeque; Pedro Cano-Ríos; Lilia Salas-Pérez; Gabriela González-Rodríguez; Arturo Reyes-González; Alma Velia Ayala-Garay; Pablo Preciado-Rangel (Terra Latinoamericana, 2020)
The vermicompost is used as a source of nutrients and substrate in protected horticulture because it promotes crop production more sustainable. The objective was to evaluate different proportions of vermicompost: sand (VC:S, v:v) on quality and yield of jalapeño pepper produced in greenhouse environments. Five proportions were compared VC:S, 1:1, 1:2, 1:3, 1:4, 1:5 and a control: (Steiner nutrient solution). The experiment was established in a randomized blocks design with ten replications. On average ratio, VC:S (1:1) produce highest fruit weight, fruit length, total phenolic compounds, flavonoids, and antioxidant capacity against to control treatment (0:1 VC:S). Those results indicate that VC is a fertilization alternative to increase nutraceutical fruit quality, without decrease the jalapeño pepper yield.